Fluorescent DNA thermotropic liquid crystal showing thermostability and water-resistance. (August 2022) - Zhang, Chenghao; Zhang, Lei; Cao, Zheng; Lian, Changshuo; Gao, Shengjie; Zhang, Di; Shi, Xue; Du, Wenjing; Xie, Congxia; Wu, Zhongtao
Abstract: Solvent-free soft biomaterials with fluorescent property are highly attractive because of their wide prospective applications in bioimaging and anticounterfeiting. However, in solvent-free condition, developing soft fluorescent DNA materials is very challenging. In this study, a type of fluorescent solvent-free DNA thermotropic liquid crystal (DNA-TPEA ) is developed via the electrostatic complexation of DNA and tetraphenylethene-containing ammonium surfactant TPEA. Under UV light, DNA-TPEA could give bright luminescence with good quantum yield, which has been tested as an anticounterfeiting labeling biomaterial working at high temperatures and in aqueous condition. An investigation on the photoluminescence lifetime of DNA-TPEA indicates that the TPEA molecules are in two different environments, and for which a working mechanism is illustrated. This work provides a new strategy for developing fluorescent biomaterials in solvent-free condition by fusing AIE surfactants and biomolecules together via electrostatic force, which gains synthetic convenience compared to the covalent modification of biomolecules with fluorescent proteins. Graphical abstract: The reported solvent-free DNA thermotropic liquid crystal could be fluorescent labeling biomaterial suitable for working at high temperatures and aqueous conditions. Image 1 Highlights: A fluorescent solvent-free DNA thermotropic liquid crystal is developed. The soft liquid crystalline DNA material would be an ideal structural biomaterial. The water-insolubility makes DNA material suitable for the application with water-resistance requirement. The excellent thermostability allows soft liquid crystalline DNA material to work in harsh conditions. The electrostatic complexation presents a convenient way for fabricating soft luminescent biomaterials.